Mendayagunakan Potensi Manusia Melalui Manajemen Qalbu Perspektif Psikologi Islam - Sukarman (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2022)
This research is a library research using a qualitative descriptive approach. This research examines how to utilize human potential bestowed by Allah through heart management. This study examines the concept of heart management from a psychological point of view, then brings together the relevance or meeting point (convergence) between heart management and Islamic psychology. The analysis of data is conducted through reduction, presentation, verification, and conclusion. The findings from this study are that the concept of heart management has relevance or convergence with Islamic psychology.